Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Pos Padang Panjang - Rusdi, Habibur; Widaningsih, Sri (eProceedings of Applied Science, 2023)
There are many competitors in the field of mail delivery services and goods delivery, so that PT Pos is experiencing a decline in customers. This study aims to examine the effect of service quality on customer satisfaction at PT. Long Field Post. By using quantitative methods obtained by distributing questionnaires directly to respondents, namely customers of the Padang Panjang post office. Data analysis in this study used validity, reliability, classic assumption tests (normality test, heteroscedasticity test), coefficient of determination R2, t test, f test. The overall data analysis used SPSS statistics 22. The results of this study lead to that: service quality partially has a positive and significant effect on customer satisfaction at the Padang Panjang Post Office Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Pos Padang Panjang Habibur Rusdi1 , Sri Widaningsih S.Psi.,MM2 Program Studi D3 Manajemen Pemasaran, Fakultas Ilmu Terapan, Universitas Telkom, Bandung, Indonesia Habiburrusdi024@gmail.com, Sri@tass.telkomuniversity.ac.id.Keywords : service quality, customer satisfaction